Effect of lycopene and metformin combination on phagocytosis, glycemic control, and oxidative stress in rats with type 2 diabetes (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Hyperglycemia and oxidative stress cause phagocytosis dysfunction in patients with diabetes. A combination of lycopene and metformin can reduce oxidative stress and blood glucose. This study aimed to determine the effect of combined lycopene and metformin on phagocytosis function, glycated hemoglobin A1c (HbA1c), nitric oxide (NO), reactive oxygen species (ROS), and advanced glycation end products (AGEs). METHODS A randomized controlled study was conducted in rats at the Center for Food and Nutrition Studies, Universitas Gadjah Mada, Yogyakarta, Indonesia, from August to September 2022. 30 rats were divided into control (n = 5) and type 2 diabetes mellitus (T2DM) (n = 25) groups. Rats in the T2DM group were induced by a high-fat diet combined with streptozotocin-nicotinamide. The 25 rats were then divided into five subgroups: 1 ml coconut oil (DM), 250 mg/kg metformin in 1 ml coconut oil (DMet), 250 mg/kg metformin + 10 mg/kg lycopene in 1 ml coconut oil (DML-10), 250 mg/kg metformin + 20 mg/kg lycopene in 1 ml coconut oil (DML-20), and 250 mg/kg metformin + 40 mg/kg lycopene in 1 ml coconut oil (DML-40). Treatments were administered daily for 4 weeks. The macrophage phagocytosis index (PI), HbA1c levels, ROS, NO, and AGEs serum were evaluated. RESULTS There was a significant difference in the PI, HbA1c, NO, ROS, and AGEs between the groups (p<0.001). The DML-20 and DML-40 groups had significantly increased PI and decreased NO, ROS, and AGEs levels than metformin alone (p<0.05). CONCLUSIONS Lycopene combined with metformin could improve phagocytosis function, glycemic control, and oxidative stress.